Quit the Project of the Development of A Device for Measuring Water Level Based on Ultrasound and Radio Wave (Eurasian Scientific Herald, 2023)
This article explores possible solutions in order to use ultrasound to accurately measuring of groundwater level or water levels in the environment. The model we provide, the highly integrated A9 GPRS Module microcircuit, can be used in a number of processes and allows for systematic temperature coupling adjustment or the construction of curves that are simple to reset. A number of applications call for the use of the A9, an ultrasonic sensor for proximity and level sensing. A number of variables can be considered to enhance the performance of the model, including the frequency of operation, power supply voltage, transducer size and shape, and the model of signal processing techniques employed. The A9 model can be improved by experimenting with various transducer sizes and shapes to ascertain.